2020
DOI: 10.1002/adbi.202000113
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Microfabricated Scaffold System for Unidirectional Cell Migration

Abstract: The present study demonstrates unidirectional cell migration using a novel 3D microfabricated scaffold, as revealed by the uneven sorting of cells into an area of 1 mm × 1 mm. To induce unidirectional cell migration, it is important to determine the optimal arrangement of 3D edges, and thus, the anisotropic periodic structures of micropatterns are adjusted appropriately. The cells put forth protrusions directionally along the sharp edges of these micropatterns, and migrated in the protruding direction. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…4). Based on this, it was possible to ascertain how cells are unevenly distributed to the right, confirming cell migration in a single direction [36].…”
Section: Confirmation Of Unidirectional Cell Migration By Uneven Dist...mentioning
confidence: 75%
See 2 more Smart Citations
“…4). Based on this, it was possible to ascertain how cells are unevenly distributed to the right, confirming cell migration in a single direction [36].…”
Section: Confirmation Of Unidirectional Cell Migration By Uneven Dist...mentioning
confidence: 75%
“…The association between micropattern shape and cell migration in a single direction, resulting in uneven cell distribution, was evaluated using time-lapse videos, which showed that 94% of cells were in the groove, and that migration toward the right (i.e., the direction from the apex angle to the base of an isosceles triangle) was high [36]. Cells in these grooves acquired characteristic adhesion morphologies that were not present on flat surfaces (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these methods have limitations in terms of coverage, as they could only span over a short distance due to the finite dynamic range of cellular sensing. To overcome this limitation, a microfabricated scaffold with a triangular shape pattern was developed to induce unidirectional cell migration [ 49 ]. This resulted in 77% of embryonic mouse fibroblast NIH3T3 cells aligned with the micropattern and migrated in one direction.…”
Section: Resultsmentioning
confidence: 99%
“…ECM alignment dictates the polarization of focal adhesions and protrusions by localizing Rac activity, which controls tumor invasiveness and modulates collective ECM remodeling through its distinct pushing/pulling deformation within diverse tumor geometry ( Wang et al, 2018 ; Kim et al, 2020 ). Cells require multiple adaptation mechanism to navigate through a more complex and restrictive in 3D microenvironment compared to 2D migration ( Figure 2B ) ( Sunami et al, 2020 ). 3D cell migration involves interactions with neighboring cells, as demonstrated via photothermal ablation of the 3D wound healing model, inhomogeneities of the 3D ECM matrix (e.g., composition and structural features), and various signaling pathways that make it a more complex process than in 2D environments ( Figure 2C ) ( Devreotes and Horwitz, 2015 ; Xiao et al, 2019 ; Hayn et al, 2020 ; Palmiero et al, 2023 ).…”
Section: Biophysical Interpretation Of Tumor Microenvironment (Tme)mentioning
confidence: 99%